Chimpanzees and death. (16th July 2018) - Anderson, James R.
Abstract : Information about responses to death in nonhuman primates is important for evolutionary thanatology. This paper reviews the major causes of death in chimpanzees, and how these apes respond to cues related to dying and death. Topics covered include disease, human activities, predation, accidents and intra-species aggression and cannibalism. Chimpanzees also kill and sometimes eat other species. It is argued that, given their cognitive abilities, their experiences of death in conspecifics and other species are likely to equip chimpanzees with an understanding of death as cessation of function and irreversible. Whether they might understand that death is inevitable—including their own death, and biological causes of death is also discussed. As well as gathering more fundamental information about responses to dying and death, researchers should pay attention to possible cultural variations in how great apes deal with death. This article is part of the theme issue 'Evolutionary thanatology: impacts of the dead on the living in humans and other animals'.